THE ANALYSIS OF RESEARCH RESULTS OF STUDENT EVALUATIONS WHEN CONSIDERING THE SECTION "ELECTROMAGNETISM" IN UNIVERSITIES - Kaliyeva , A.A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article is devoted to the analysis of the results of students ' assessment studies when considering the section of electromagnetism in Universities. The urgency of introduction of modern system of control of knowledge is shown. The main purpose of the educational work of these universities is to implement a comprehensive system of professional training of highly qualified specialists, allowing them to be in demand in any of the above areas of engineering. It is proved that the quality of education is one of the priorities in Universities. Based on the results of the study, a new system of knowledge control is proposed. The comparison of system and traditional approach of mastering by students ' materials is considered, the analysis of research results is carried out. Also, as a result of the research, a comparative analysis of the evaluation results for different Universities in different countries was carried out.